ANALISIS KETERKAITAN KESEHATAN MENTAL DAN STRES AKADEMIK MAHASISWA - Rahmadi, M. Agung; Nasution, Helsa; Mawar, Luthfiah; Sari, Milna (Counseling For All : Jurnal Bimbingan dan Konseling, 2024)
This study analyzes the relationship between mental health and academic stress among students through a systematic literature synthesis and meta-analysis. The meta-analysis of 127 studies involving a total of 89,632 participants reveals a strong positive correlation between academic stress and indicators of mental health, including depression (r = 0.48), anxiety (r = 0.45), and general psychological stress (r = 0.52). Moderator analysis indicates variation in score differences based on gender, geographic region, and time. The identified mediating mechanisms include maladaptive coping strategies, poor sleep quality, and low perceived social support. Furthermore, longitudinal studies demonstrate a lagged effect of academic stress on symptoms of depression and anxiety. On the other hand, meta-analysis of interventions shows moderate effectiveness in reducing academic stress and improving mental health. These findings emphasize the importance of a holistic approach to addressing academic stress and student mental health, consistent with previous theoretical models, such as the diathesis-stress theory and conservation of resources theory. Lastly, the presentation of comprehensive synthesis results and robust quantitative analysis regarding the relationship between academic stress and student mental health identifies previously unexplored moderator and mediator factors. Additionally, the longitudinal perspective on the dynamics of the relationship between these two variables represents another novelty. The results of this study are expected to have implications for educational institutions, policymakers, and mental health practitioners.